2003
DOI: 10.1385/ni:1:4:343
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Correlates of Gene Expression in Recombinant Inbred Strains: A Relational Model System to Explore Neurobehavioral Phenotypes

Abstract: Full genome sequencing, high-density genotyping, expanding sets of microarray assays, and systematic phenotyping of neuroanatomical and behavioral traits are producing a wealth of data on the mouse central nervous system (CNS). These disparate resources are still poorly integrated. One solution is to acquire these data using a common reference population of isogenic lines of mice, providing a point of integration between the data types. Recombinant inbred (RI) mice, derived through inbreeding of progeny from a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
108
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 118 publications
(109 citation statements)
references
References 23 publications
1
108
0
Order By: Relevance
“…29,30 We employed the approach to identify genes and biological processes that are associated with cytoarchitectural abnormalities found in the PFC of major psychiatric disorders. Our functional annotation analysis revealed that multiple biological processes including cell metabolism, neurodevelopment, cell motility and programmed cell death were commonly associated with the prefrontal cytoarchitectural deficits of perineuronal oligodendrocytes (Table 4) and calbindin-positive GABAergic neurons (Table 5).…”
Section: Discussionmentioning
confidence: 99%
“…29,30 We employed the approach to identify genes and biological processes that are associated with cytoarchitectural abnormalities found in the PFC of major psychiatric disorders. Our functional annotation analysis revealed that multiple biological processes including cell metabolism, neurodevelopment, cell motility and programmed cell death were commonly associated with the prefrontal cytoarchitectural deficits of perineuronal oligodendrocytes (Table 4) and calbindin-positive GABAergic neurons (Table 5).…”
Section: Discussionmentioning
confidence: 99%
“…We then performed an in silico analysis of the relation between MBD2 expression and that of the GR gene using data hippocampal expression analyses with recombinant mouse strains available through the NIH-supported project (http://www.genenet work.org) [29]. The GeneNetwork database contains data …”
Section: Gr Promotermentioning
confidence: 99%
“…genetic structure of the RI strains will enable us to establish networks of functionally important relationships within and among diverse sets of physiological and behavioral phenotypes 13,14 . Gene-environment interaction is a crucial problem in genetics, and a key contributor to most common diseases, which has been difficult to study in any mammalian population.…”
Section: What Kind Of Science Will It Enable?mentioning
confidence: 99%